PENGARUH WORD OF MOUTH TERHADAP BRAND LOYALTY MELALUI BRAND TRUST DAN CUSTOMER SATISFACTION PADA MASKAPAI PENERBANGAN LOW COST CARRIER - Harisky, Martinus Shon (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The low cost carrier is the controversial airlines because the airlines applied lower price but the airlines incident higher than regulary airlines. The purpose of this research is to identify the influence of WOM towards customer satisfaction and brand trust, to identify the influences of customer satisfaction and brand trust towards brand loyalty. The number of samples are 150 samples, but there are two sample with outlier, so the samples is used 148 samples. The data analysis technique ia structural equation model. The research showing that WOM have impact towards customer satisfaction and brand trust, customer satisfaction and brand trust have impact towards brand loyalty. Customer satisfaction and brand trust able to mediate the influences WOM towards brand loyalty.